1984
DOI: 10.1111/j.1365-2311.1984.tb00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Species packing and temperature dependent competition among burying beetles (Silphidae, Nicrophorus)

Abstract: Abstract. 1. Burying beetles are carrion feeders that specialize on small carcasses. We investigated interactions among congeners at two sites in Michigan, U.S.A., that differ in both number and relative proportion of species. 2. Intra‐ and interspecific competition for carcasses is intense. The majority of carcasses are found within 24 h of their placement. 3. Competition between N.arbicollis and N.defodiens is temperature dependent. N.orbicollis can displace N.defodiens on single carcasses, but requires war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 13 publications
3
118
0
Order By: Relevance
“…As one example, I have studied four coexisting species of carrion beetles (Silphidae, Nicrophorus), all of whom reproduce exclusively on small carcasses such as dead mice. This is about as narrow a niche as one can imagine, but still the species coexist only by being different --in their seasonal activity, their diurnal activity, their patterns of overwintering, and so on (Wilson et al 1984).…”
Section: Mental Representations As Species Of Thought In Interacting mentioning
confidence: 99%
“…As one example, I have studied four coexisting species of carrion beetles (Silphidae, Nicrophorus), all of whom reproduce exclusively on small carcasses such as dead mice. This is about as narrow a niche as one can imagine, but still the species coexist only by being different --in their seasonal activity, their diurnal activity, their patterns of overwintering, and so on (Wilson et al 1984).…”
Section: Mental Representations As Species Of Thought In Interacting mentioning
confidence: 99%
“…Examples include species pairs of Collembola (Kaczmarek, 1975;Longstaff, 1976;Greenslade and Greenslade, 1980;Sparkes, 1982 andHagvar, 1990), cryptostigmatid mites (Anderson, 1978b) and ants (Culver, 1974;Davidson, 1985). Strong interspecific competition for ephemeral resources of dung in sub-tropical habitats (Anderson and Coe, 1974;Ridsdill-Smith et al, 1982;Giller and Doube, 1989) and carrion in tropical and temperate habitats (Wilson et al, 1984;Hanski, 1987 andTrumbo, 1990) has been readily identified. Most of these studies have indicated strong asymmetric competition (e.g.…”
Section: Diversity Of Food Resources and Trophic Speciafizationmentioning
confidence: 99%
“…(Morgan, 1987). There is also evidence to suggest that there are differential tolerances to environmental temperatures among Nicrophorus species (Wilson et al, 1984;Trumbo, 1990;Sikes, 1996;Scott, 1998), which may be related to factors such as body size, pigmentation or evolutionary history and may play a role in species distributions and coexistence. Sympatric species that utilize different thermal and temporal windows for activity have been shown to coexist in the same habitat types without much direct contact (Wilson et al, 1984), and larger species in northern Europe and northeastern North America have been shown to be nocturnal (Scott, 1998).…”
mentioning
confidence: 99%